The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3748/wjg.v23.i21.3784
|View full text |Cite
|
Sign up to set email alerts
|

New endoscopes and add-on devices to improve colonoscopy performance

Abstract: Colonoscopy is the gold standard for colorectal cancer prevention; however, it is still an imperfect modality. Precancerous lesions can be lost during screening examinations, thus increasing the risk of interval cancer. A variety of factors either patient-, or endoscopist dependent or even the procedure itself may contribute to loss of lesions. Sophisticated modalities including advanced technology endoscopes and add-on devices have been developed in an effort to eliminate colonoscopy’s drawbacks and maximize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Utilising technological adjuncts to augment ADRs have been explored[ 29 , 30 ]. High definition imaging and selective application of dyes are not useful in increasing ADRs[ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Utilising technological adjuncts to augment ADRs have been explored[ 29 , 30 ]. High definition imaging and selective application of dyes are not useful in increasing ADRs[ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many technical modifications have been trialled with regard to the polyp and adenoma detection rates [6]. While withdrawal time appears to be an important factor influencing polyp and adenoma detection rates [7], innovations of technology may have a small but significant effect on polyp and subsequent adenoma detection rates [6].…”
Section: Discussionmentioning
confidence: 99%
“…While withdrawal time appears to be an important factor influencing polyp and adenoma detection rates [7], innovations of technology may have a small but significant effect on polyp and subsequent adenoma detection rates [6]. Technological improvements include widened fields of view, incorporation of more than one camera that allows simultaneous image transmission or add-on attachable devices on standard colonoscopes that facilitate the detection of lesions in the proximal aspect of colonic folds [6]. As an example, a recent systematic review assessing the effects of Endocuff ® concluded that the use of this device significantly improved pre-cancerous polyp detection from 43.3 to 50.4% [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate bowel preparation, lack of physician’s expertise, inability to accurately visualize the colonic mucosa located proximal to the haustral folds or in proximity to anatomic flexures have been listed among the main reasons such lesions can be missed during a colonoscopy[ 12 ]. Lately, several devices-ranging from complex endoscopic systems to simple plastic attachments- have been developed, in an attempt to address this problem[ 13 ]. They promise to flatten the mucosa during scope withdrawal and facilitate maneuverability around anatomic flexures offering meticulous mucosal visualization and detection of “hidden” lesions.…”
Section: Introductionmentioning
confidence: 99%